2016
DOI: 10.3389/fncel.2016.00114
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Gamma Aminobutyric Acid Receptors (GABAAR) by Ethanol: How Are Inhibitory Receptors Affected?

Abstract: In recent years there has been an increase in the understanding of ethanol actions on the type A γ-aminobutyric acid chloride channel (GABAAR), a member of the pentameric ligand gated ion channels (pLGICs). However, the mechanism by which ethanol potentiates the complex is still not fully understood and a number of publications have shown contradictory results. Thus many questions still remain unresolved requiring further studies for a better comprehension of this effect. The present review concentrates on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 198 publications
(259 reference statements)
1
46
0
Order By: Relevance
“…Ionotropic Glutamate Receptors (iGluRs) are ligand-gated ion channels (LGICs), which are well characterized targets for EtOH actions (Forstera et al, 2016; Lovinger, 1997; Szumliski and Woodward, 2014; Vengeliene et al, 2008). LGICs are heteromeric proteins that bind extracellular neurotransmitters or intracellular messengers and transduce that binding energy into the opening of an intrinsic ion pore (Collingridge et al, 2009).…”
Section: 1 Glutamate and Etoh Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ionotropic Glutamate Receptors (iGluRs) are ligand-gated ion channels (LGICs), which are well characterized targets for EtOH actions (Forstera et al, 2016; Lovinger, 1997; Szumliski and Woodward, 2014; Vengeliene et al, 2008). LGICs are heteromeric proteins that bind extracellular neurotransmitters or intracellular messengers and transduce that binding energy into the opening of an intrinsic ion pore (Collingridge et al, 2009).…”
Section: 1 Glutamate and Etoh Effectsmentioning
confidence: 99%
“…There are 3 main types of GABA receptors; GABA A R and GABA C R are LGICs, while the GABA B R is a GPCR (Aguayo et al, 2002; Forstera et al, 2016; Harris, 1999; Lovinger, 1997). Early rodent studies showed that systemic administration of GABA A R agonists increased voluntary EtOH consumption, whereas GABA A R antagonists and benzodiazepine inverse agonists decreased drinking (Boyle et al, 1993; Rassnick et al, 1993).…”
Section: 2 Gaba and Etoh Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of alcohol action, however, has presented a great challenge for mechanistic investigation. Alcohols act on various proteins by different mechanisms (Deitrich et al, 1989; Forstera et al, 2016). Pentameric ligandgated ion channels (pLGICs) in the CNS, which include the inhibitory glycine receptors (GlyRs) and γ-aminobutyric acid type A receptors (GABA A Rs), and the excitatory serotonin receptors (5HT 3 Rs) and nicotinic acetylcholine receptors (nAChRs), are plausible molecular targets of linear alcohols ( n -alcohols).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of alcohol action, however, has presented a great challenge for mechanistic investigation. Alcohols act on various proteins by different mechanisms (Deitrich et al, 1989;Forstera et al, 2016). Pentameric ligandgated ion channels (pLGICs) in the CNS, which include the inhibitory glycine receptors (GlyRs) and γ-aminobutyric acid type A receptors (GABA A Rs), and the excitatory serotonin receptors (5HT 3 Rs) and nicotinic acetylcholine receptors (nAChRs), are plausible molecular targets of linear alcohols (nalcohols).…”
Section: Introductionmentioning
confidence: 99%